Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Charles Trudrung Taylor, Rae Blanco, Rebecca Patch, Robert Patch, Julie Silva, Brad Silva, Judge Denise Whitehead, and Steve Whitehead